Prognostic relevance of Ki-67 and P16/INK4a markers in histological diagnosis of cervical dysplasia - T. A. Dimitriadi; D. V. Burtsev; E. A. Dzhenkova; T. N. Gudtskova; K. V. Dvadnenko (Исследования и практика в медицине)
Purpose of the study. To determine the quantitative parameters of the molecular markers Ki‑67 and p16/INK4a at CIN 1–3 and to establish the possibility of using them to improve the quality of diagnosis by histological samples.Patients and methods. Biopsy material of the cervix was studied in 71 patients who were carriers of HPV infection. Immunohistochemical method (IHC) in biopsy specimens determined the expression of Ki‑67 and p16/INK4a markers.Results. According to the results of a standard histological examination, the distribution of patientsinto groups occurred as follows: CIN 1–18, in CIN 2–39, in CIN 3–14 patients. It was found that the expression of the studied markers is associated with the severity of dysplastic changes in the tissue of the cervix. By the studied marker, the most characteristic molecular profiles for the degrees of dysplasia were determined: CIN1 – Ki‑67–15–25%, p16/INK4a 10–15%; CIN2 – Ki‑67–70–80%, p16/INK4a – 65–70%; CIN3 – Ki‑67–85–90%, p16/INK4a – 90–95%. Heterogeneity was revealed in the expression of these markersin the CIN 2 group: in 7 cases (22,6%), the molecular profile corresponded to CIN 1, in 1 case (3,6%) to CIN 3. Clinical examples of using the IHC profile to clarify the degree of CIN are given.Conclusion. The use of an IHC study with Ki‑67 and p16/INK4a, in addition to the standard histological examination, makes it possible to objectify the initial diagnosis of the degree of CIN, as well as to identify patients with a high and low risk of developing severe injuries. This is especially true for the CIN2 group, the most problematic in terms of histological evaluation and tactics of clinical management of patients. The use of IHC in the initial diagnosis will contribute to: improving the information content of multiple aimed and loop excisional biopsies; reduction in relapse due to inadequate treatment; eliminating the unreasonable use of such a traumatic method as conization (especially in women of childbearing age).